Common Fixed Point Theorem for Hardy-Rogers Contractive Type in Cone 2-Metric Spaces and Its Results - Hardan, Basel; Patil, Jayashree; Hamoud, Ahmed A.; Bachhav, Amol (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, Hardy-Rogers type common fixed point theorem of self contractive maps in cone 2-metric spaces over Banach algebra is proved. The corresponding conclusions in the literature are improved and generalize by obtained results. Some examples proposed to illustrate our main results.